2019
DOI: 10.1002/jpln.201800586
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fertilization on cover crops and microbial community on a bauxite‐mined soil undergoing reclamation

Abstract: The reclamation of bauxite‐mined areas can be favored by the application of organic and/or chemical fertilization to restore the vegetation. Otherwise, the impact of fertilizations on soil microbiota or plant–microbe interactions as land reclamation progresses is less understood. To address this issue, we evaluated the impact of organic and chemical fertilization on plants and soil microbial community within the first 36 months of land reclamation in a bauxite‐mined site. The experiment was set up according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In practice, immature soil can be modified by adding organic matter and PGP microbes to promote soil maturity and plant growth ( Larney and Angers, 2012 ; Rashid et al, 2016 ; Li et al, 2021a ). Over the last few years, the continued application of organic amendments, such as planting winter legume crops, promoting the use of commercial organic fertilizer, utilizing animal manure, was carried out to improve the soil quality of newly reclaimed land ( Drozdowski et al, 2012 ; Watkinson et al, 2017 ; Teixeira et al, 2019 ). Recently, PGPF-based biofertilizers have attracted significant attention due to the environment friendly and agriculture sustainability abilities ( Egamberdieva and Adesemoye, 2016 ; Hossain and Sultana, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, immature soil can be modified by adding organic matter and PGP microbes to promote soil maturity and plant growth ( Larney and Angers, 2012 ; Rashid et al, 2016 ; Li et al, 2021a ). Over the last few years, the continued application of organic amendments, such as planting winter legume crops, promoting the use of commercial organic fertilizer, utilizing animal manure, was carried out to improve the soil quality of newly reclaimed land ( Drozdowski et al, 2012 ; Watkinson et al, 2017 ; Teixeira et al, 2019 ). Recently, PGPF-based biofertilizers have attracted significant attention due to the environment friendly and agriculture sustainability abilities ( Egamberdieva and Adesemoye, 2016 ; Hossain and Sultana, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The productive capacity of the newly reclaimed land often needs 7-10 years of fertilization to basically reach the level of occupied cultivated land. In the actual production practice, we can improve the quality of newly reclaimed land by acidification adjustment, planting green manure, returning straw to field, comprehensive utilization of agricultural and animal husbandry wastes, using rural litter to make compost, and promoting the use of commercial organic fertilizer [7][8][9][10][11][12][13]. Indeed, the improvement of these measurements in soil quality may be mostly due to their increase in the content of soil organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the soil suitability of newly reclaimed land is highly associated with the content of the soil organic matter, which can strengthen the ability of the soil to maintain and supply fertilizer, change the structure of soil aggregates, and enhance soil fertility. Specifically, more and more studies have shown that the quality of newly reclaimed land and the content of soil organic matter could be effectively improved by increasing the use of organic fertilizer, such as planting winter legume crops; returning crop stems and stalks to the field; promoting the use of commercial organic fertilizer; comprehensively utilizing agricultural and animal husbandry wastes; and making compost by using rural litter, other plant residues, and gully soil [7][8][9][10][11][12][13]. Therefore, it can be inferred that organic fertilizers are, in general, ideal conditioners for newly reclaimed soil.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the production capacity of reclaimed land is only 10−30% of the occupied cultivated land in China (Wang et al, 2017 ), and it often needs 7–10 years of fertilization to reach the level of occupied cultivated land, including acidification adjustment, returning straw to the field, planting green manure, and comprehensive utilization of COF and animal manure (Rendana et al, 2018 ; Teixeira et al, 2019 ; Li et al, 2021b ). In other words, the content of soil organic matter is highly associated with soil suitability, and the quality of new reclamation land can be effectively improved by increasing the use of organic fertilizers.…”
Section: Discussionmentioning
confidence: 99%